Psychometric properties of The Revised Rape Myth Acceptance Scale–Indonesian version (rIRMA-Indonesian) - Isa, Tsania M.; Shanti, Theresia Indira; Sumampouw, Nathanael E.J.; Agustian, Murniati (Faculty of Psychology, Universitas Diponegoro, 2026)
Background: Rape myths are inaccurate beliefs that legitimize sexual violence through victim-blaming and perpetrator justification. Rape myth acceptance (RMA) is linked to sexual violence perpetration and underreporting by victims and is shaped by broader cultural norms and power relations, emphasizing the need for culturally sensitive measurement tools.Purpose: In line with Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi’s 2024 PPKPT policy on preventing and addressing sexual violence in higher education, this study examines the construct validity and reliability of the Revised Illinois Rape Myth Acceptance Scale Adapted for Indonesia (rIRMA-Indonesian).Method: Using an online survey of 504 participants (ages 15–61), which includes students, lecturers, and Satgas PPKS members. Exploratory along with confirmatory factor analyses and reliability testing were conducted based on the revised three-factor rIRMA model.Findings: Results supported a theoretically coherent three-factor structure with strong internal consistency, although elevated RMSEA values and high inter-factor correlations suggested partial construct overlap.Implications: The findings indicate a culturally convergent rape myth belief system in Indonesia shaped by gender, moral norms, and authority structures, while the rIRMA-Indonesian provides an empirically grounded tool for higher education institutions and policymakers under the PPKPT framework.Limitations: Model fit concerns and cultural convergence across factors indicate the need for further culturally informed refinement beyond item reduction.